Smart Cities in comparison: An analysis of the best Smart Cities - Stefano CARBONI (Smart Cities and Regional Development Journal, 2024)
This research paper aims to identify the best Smart City in the world, by investigating the rankings of Smart Cities, based on its main characteristics and implemented policies. The purpose of this study is to provide a comprehensive understanding of what makes a city “Smart” and to highlight the successful strategies employed by the top-ranked Smart Cities. The research employs a qualitative analysis approach, utilizing thematic maps created with the QGIS software. This methodology allows for a detailed examination of various factors contributing to a Smart City’s status, including but not limited to, technological integration, sustainable practices, and citizen participation. The expected results of this study is to report and analyze the best smart cities, according to the Smart City rankings, and also to shed light on the key elements and policies that contribute to their success. These findings could serve as a benchmark for other cities striving to achieve ‘Smart’ status. Furthermore, the thematic maps will visually represent the distribution and implementation of Smart policies, providing a clear and comprehensive overview of the Smart landscape in the top-ranked cities. This research has the potential to contribute to the field of urban development and planning, particularly in the context of Smart Cities. It could guide policymakers and city planners in designing and implementing effective strategies to transform their cities into more sustainable, efficient, and livable spaces.